Adverse drug reactions in children and adolescents on daily antitubercular regimen: An observational longitudinal study - Agarwal, Anurag; H B, Sharadhi; Mathur, Surendra Bahadur; Kalra, Bhupinder Singh; Arora, Reema; Khanna, Ashwani; Rajeshwari, K. (Indian journal of tuberculosis, 2023)
Subsequent to introduction of daily fixed dose combination (FDC) regimen with increased dosages and inclusion of ethambutol in continuation phase of antitubercular therapy (ATT) in India, this study was done to evaluate adverse drug reactions (ADRs) in children and adolescents. Longitudinal observational study conducted in tertiary teaching hospital. Children (1 month–18 year), with newly diagnosed drug sensitive tuberculosis, started on daily FDC regimen of ATT, were included. Participants were followed up at 2 weeks, 8 weeks and 6 months. Division of AIDS (DAIDS) severity grading and World Health Organization-Uppsala Monitoring Centre (WHO-UMC) causality assessment was done. In 99 participants, 29 experienced ADRs. Most commonly ADRs involved hepatobiliary (11.1%) and gastrointestinal (8.1%) systems. Grade 3 severity noted in 35.5% ADRs. Certain causality classified in 19.3%. Presence of ADRs was significantly higher in participants with vs without malnutrition [40.5% vs 21.1% (p = 0.036)]. Tendency for more severe ADRs noted in participants with vs without malnutrition [Grade 3 ADRs out of all ADRs: 64.7% vs 0% (p < 0.001)]. Incidence and severity of ADRs has increased after introduction of daily FDC of ATT. Most common ADR observed were hepatobiliary. Malnutrition and less weight for age were risk factors for occurrence and severity of ADRs. •The incidence of ADRs has increased after the introduction of daily FDC of ATT as compared to alternate day regimen.•ATT induced hepatotoxicity was the most common ADR observed in the pediatric age group.•The severity of the ADRs was also found to be increased as compared to alternated day regimen.•Malnutrition and less weight for age were risk factors for occurrence and severity of ADRs.